Pathogenic Roles of Macrophage Migration Inhibitory Factor during Dengue Virus Infection - Yung-Chun Chuang; Hong-Ru Chen; Trai-Ming Yeh (Mediators of Inflammation)
Dengue virus (DENV) infection is the most common cause of viral hemorrhagic fever, which can lead to life-threatening dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Hemorrhage and plasma leakage are two major hallmarks of DHF/DSS. Because the mechanisms causing these pathogenic changes are unclear, there is no effective therapy against DHF/DSS. In this review, we focus on the possible pathogenic effects of a pleiotropic cytokine, macrophage migration inhibitory factor (MIF), on the pathogenesis of DENV infection. MIF is a critical mediator of the host immune response and inflammation, and there is a correlation between the serum levels of MIF and disease severity in dengue patients. Furthermore, MIF knock-out mice exhibit less severe clinical disease and lethality. However, the role of MIF in the pathogenesis of DHF/DSS is not limited to immune cell recruitment. Recent evidence indicates that DENV infection induced MIF production and may contribute to vascular hyperpermeability and viral replication during DENV infection. The expression of both adhesion and coagulation molecules on MIF-stimulated monocytes and endothelial cells is also increased, which may contribute to inflammatory and anticoagulatory states during DHF/DSS. Therefore, blocking MIF production or its function may provide a solution for the treatment and prevention of DHF/DSS.